Work instability. Presentation of an empirical model about its psychological impact - Maglio, Ana Laura; Injoque-Ricle, I.; Leibovich de Figueroa, Nora (2010)
Research on the impact that work instability has on workers has the limitation of assess the relations among different variables separately, without examining the possible mediation relationships that can exists between them. The aim of this article is to test a conceptual model of the mediating relations between the uneasiness due to work instability and the psychological impact, in the framework of interactive stress theory, conducting a Path Analysis. 191 workers participated on the study, with a mean age of 31 years-old (SD = 11). Results showed that the proposed model didn't fit to the data. Alternative models were explored, consistent with the original conceptual model and the empiric evidence. A new causal model is proposed, where Uneasiness due to Work Instability as an independent variable, Personal Strain and Personal Resources as intervenient variables, and Anger, Hopelessness, and Satisfaction as dependent ones. The theoretical and empirical importance of the resulting model is discussed.
Keywords: Work Instability; Psychological Impact; Conceptual Model; Path Analysis; Estabilidad; Planificación laboral; Trabajo; Stress